ANALISIS TERHADAP PERKEMBANGAN DAN KONSEP FIKIH LINGKUNGAN DALAM KITAB ULAMA BANJAR - Sukarni, Sukarni; bin Mahmud, Hafini (Syariah: Jurnal Hukum dan Pemikiran, 2024)
This research is motivated by the increasing importance of seeking efforts for environmental safety as the main support for human survival. The aspect of religious thought (fiqh) is one of them. The Banjar people, especially those who live in South Kalimantan, as the land of Mecca's verandas, the land of a thousand mosques, and the city of Islamic students, have undoubtedly given birth to many works of Islamic legal thought. Based on the results of the search, in the books of Banjar Islamic jurisprudence from the XVIII, XIX and XX centuries AD, there are 10 books by Banjar Islamic scholars, of which the 10 (ten) Banjar Islamic jurisprudence books mostly discuss muamalah, worship and law. So the research aims to analyze the development and concepts of environmental jurisprudence in the Islamic jurisprudence works of Banjar ulama in the contemporary era. The method used according to type is library research with a historical, hermeneutical and istinbath approach because the focus of the study in this research is environmental jurisprudence thinking on the jurisprudence of the work of Banjar ulama. The research results show that there are no books by South Kalimantan (Banjar) ulama that discuss environmental jurisprudence. The works of this banjar cleric include the Books of Sabilal Muhtadin, Parukunan Jamaluddin, USSA, Parukunan Melayu Besar, Asrar as-Salat, Risalat Rasam Parukunan, Mabadi Ilmu Fiqh, Risâlah Mu'âmalât, Is'af al-Haidh book, and Tangga Ibadah. From several of these books, it can be seen that the development of the concept of environmental jurisprudence is not yet visible. The jurisprudential aspect of worship dominates the discussion pages. Water issues and agricultural land conservation (environmental aspects) have been discussed in several books, but the descriptions have not shown positive developments.